An approach to identify the weak parts of stiffness for the machine tool cantilever structure. (January 2022) - Guo, Tieneng; Meng, Lingjun; Cao, Jinxuan; Bai, Chunsheng
Investigating weak parts of the structure is one of the most important issues for improving the stiffness of the machine tool. However, studies show that overcoming the static deformation is a challenging problem in practical structures. In the present study, the dynamic hammer testing approach is applied to analyze the cantilever structure of the machine tool with elastic support. Accordingly, a new weakness index (WI) is proposed to identify weak parts of the cantilever structure with an elastic support. Then the cantilever beam with the elastic support is numerically simulated and weak parts are modeled as stiffness reduction. In this regard, finite element (FE) simulations are carried out to evaluate the effectiveness of the WI method in several scenarios with single and multiple weaknesses, including the noise case. In the combined structure of the tailstock and the bed of the machine tool, sensors are utilized to collect vibration data. Furthermore, the dynamic characteristics are calculated through the modal state-space method to obtain the stiffness data at zero-frequency. Then, weak parts of the structural stiffness are identified based on the weakness index. It is found that the FE simulations are in an excellent agreement with the experiment. Therefore, it is proved that the WI can accurately identify the weak parts of the machine tool cantilever structure.